EQTL Regulating Transcript Levels Associated with Diverse Biological Processes in Tomato . Issue 1 (14th July 2016) - Ranjan, Aashish; Budke, Jessica M.; Rowland, Steven D.; Chitwood, Daniel H.; Kumar, Ravi; Carriedo, Leonela; Ichihashi, Yasunori; Zumstein, Kristina; Maloof, Julin N.; Sinha, Neelima R.
Abstract : Genetic mapping and coexpression highlights hot spots regulating transcripts linked to diverse biological processes. Abstract: Variation in gene expression, in addition to sequence polymorphisms, is known to influence developmental, physiological, and metabolic traits in plants. Genetic mapping populations have facilitated identification of expression quantitative trait loci (eQTL ), the genetic determinants of variation in gene expression patterns. We used an introgression population developed from the wild desert-adapted Solanum pennellii and domesticated tomato ( Solanum lycopersicum ) to identify the genetic basis of transcript level variation. We established the effect of each introgression on the transcriptome and identified approximately 7, 200 eQTL regulating the steady-state transcript levels of 5, 300 genes. Barnes-Hut t -distributed stochastic neighbor embedding clustering identified 42 modules revealing novel associations between transcript level patterns and biological processes. The results showed a complex genetic architecture of global transcript abundance pattern in tomato. Several genetic hot spots regulating a large number of transcript level patterns relating to diverse biological processes such as plant defense and photosynthesis were identified. Important eQTL regulating transcript level patterns were related to leaf number and complexity as well as hypocotyl length. Genes associated with leaf development showed an inverse correlation with photosynthetic gene expression, but eQTL regulating genes associated with leaf development and photosynthesis were dispersed across the genome. This comprehensive eQTL analysis details the influence of these loci on plant phenotypes and will be a valuable community resource for investigations on the genetic effects of eQTL on phenotypic traits in tomato.